2015
DOI: 10.1007/s11661-015-3079-x
|View full text |Cite
|
Sign up to set email alerts
|

Dissimilar Laser Welding/Brazing of 5754 Aluminum Alloy to DP 980 Steel: Mechanical Properties and Interfacial Microstructure

Abstract: A diode laser welding/brazing technique was used for lap joining of 5754 aluminum alloy to DP 980 steel with Al-Si filler metal. The correlation between joint interfacial microstructure, wettability of filler metal, and mechanical properties was systematically investigated. At low laser power (1.4 kW), a layer of intermetallic compounds, composed of h-Fe(Al,Si) 3 and s 5 -Al 7.2 Fe 1.8 Si, was observed at the interface between fusion zone and steel. Because of the poor wettability of filler metal on the steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…The authors found maximum joint strength of 180 N mm -1 with phase layer thickness around 2 ~ 3 ㎛. Yang et al 24) used heat input of around 70 ~ 168 J mm -1 to join 2 mm thick AA5754 alloy and 1 mm thick galvanized DP980 steel sheets by diode laser beam using AA4047 filler wire. Fig.…”
Section: Laser Beam Based Joiningmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors found maximum joint strength of 180 N mm -1 with phase layer thickness around 2 ~ 3 ㎛. Yang et al 24) used heat input of around 70 ~ 168 J mm -1 to join 2 mm thick AA5754 alloy and 1 mm thick galvanized DP980 steel sheets by diode laser beam using AA4047 filler wire. Fig.…”
Section: Laser Beam Based Joiningmentioning
confidence: 99%
“…At a medium heat input of 120 J mm -1 , the joint strength was Heat input (J mm -1) Phase layer thickness (㎛) Heat input(J mm -1 ) Joint strength (N mm -1 ) Fig. 2 Influence of heat input on joint strength in laser beam joining of AA5754 alloy and galvanized DP980 steel sheets 24) 대한용접․접합학회지 제36권 제5호, 2018년 10월…”
Section: Laser Beam Based Joiningmentioning
confidence: 99%
“…Chemical compositions of some Al/Fe and Al/Fe/Si IMCs are listed in Table 6 based on the (Song et al, 2009) literature findings. It was noticed that the chemical composition of 5G-1 was found to be similar to Al 7.2 Fe 1.8 Si phase as mentioned in (Song et al, 2009;Yang et al, 2015). According to Al-Fe binary phase diagram, Fe 2 Al 5 compound contains 53-57 wt.% aluminum (Kattner and Burton, 1992).…”
Section: Chemical Analysis Of Intermetallic Phasesmentioning
confidence: 86%
“…Figner et al (2009) examined the friction stir spot welding of aluminum AA5754 and galvanized steel HX 340LAD. Yang et al (2015) studied lap joining of AA5754 to DP 980 steel by diode laser welding and investigated the correlation between interfacial microstructure and mechanical properties. They obtained a hard and a brittle Fe 2 (Al,Si) 5 (η phase) with micro cracks between steel and aluminum at high laser power.…”
Section: Introductionmentioning
confidence: 99%
“…Their chemical compositions and mechanical properties are given in Tables 1 and 2 Base materials were machined as rectangular strips of 50 × 60 mm 2 . The aluminum alloy sheets went through a very strict two-step cleaning process, which was shown in our previous study [19]. The steel sheets were cleaned in acetone, and then ground to 1000 grit using SiC abrasive paper and again ultrasonically cleaned in acetone.…”
Section: Methodsmentioning
confidence: 99%